Перспективы влияния искусственного интеллекта на прекариатизацию научных сотрудников и педагогических работников - Слободская, Анастасия Валерьевна (Социосфера)
The article addresses the issue of the impact of rapid technological development on the social structure of society and labor relations in it. It demonstrates how automation of production has led to the precariatization of manual workers, and the spread of distance learning has become a factor in the destabilization of labor relations in terms of the spread of short-term contracts for teachers-developers of online courses. In accordance with the specifics of the implementation and prospects for the use of artificial intelligence technology, factors contributing to the intensification of precariatization in the field of education and science were identified.